1992
DOI: 10.1111/j.1360-0443.1992.tb01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of drunkenness of customers leaving licensed premises in Perth, Western Australia: a comparison of high and low ‘;risk’ premises

Abstract: A measure of the risk of licensed premises having customers involved in road traffic accidents and drink-driving offences was utilised in order to identify seven 'High Risk' and eight 'Low Risk' premises in metropolitan Perth, Western Australia. This measure, or 'Risk Ratio', was defined as the ratio of incidents of alcohol-related harm to an estimate of on-premises alcohol sales for a particular establishment. A study was conducted to test the hypothesis that a High Risk status would be associated with greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 5 publications
2
13
1
1
Order By: Relevance
“…The most frequently reported quantity of beer, 16 units per occasion, was twice that of the most frequently reported quantity of spirits and more than four times the most frequently reported quantity of wine. This result offers support to the findings that beer drinkers observed in a natural setting consumed about three times as much as spirit drinkers (Stockwell et al, 1992). The present study also supports the findings that males consume more beer than do females.…”
Section: Discussionsupporting
confidence: 90%
“…The most frequently reported quantity of beer, 16 units per occasion, was twice that of the most frequently reported quantity of spirits and more than four times the most frequently reported quantity of wine. This result offers support to the findings that beer drinkers observed in a natural setting consumed about three times as much as spirit drinkers (Stockwell et al, 1992). The present study also supports the findings that males consume more beer than do females.…”
Section: Discussionsupporting
confidence: 90%
“…This non‐participant observation study identified alcohol‐related affordances related to: alcohol access, regulations, furnishing, alternative opportunities for action, décor and lighting, drink and accessory availability, and action opportunities provided by others. Many of these identified features have been associated with increased, problematic consumption and alcohol‐related harm within previous research (e.g., Doherty & Roche, ; Gruenewald, ; Homel & Clark, ; Hughes et al., , ; Kilfoyle & Bellis, ; Livingston, ; Miller et al., ; Nusbaumer & Reiling, ; Stockwell et al., , ; Toomey et al., ; Wagenaar et al., ). These findings further support the idea that contextual features may influence alcohol consumption, which could help address some of the limitations of dominant social cognition models focusing solely on cognitive determinants of behaviour when looking to prevent alcohol misuse (e.g., Gerrard et al., ; Vlaev & Dolan, ; Webb & Sheeran, ).…”
Section: Discussionmentioning
confidence: 61%
“…Research has shown that certain aspects of the physical environment of a licensed establishment increase the likelihood that drinking will be associated with problems (Graham et al, 1997), the general characteristics of the barroom environment (Homel & Clark, 1994), and the general type of bar (Gruenewald et al, 1999; Stockwell et al, 1992). The focus on high-risk physical environments, such as licensed premises, has several advantages.…”
Section: Design Of a Prevention Approach For Music Venuesmentioning
confidence: 99%